(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Mihaela Gheorghe explores the internal Hell of the writer in J.M. Coetzee’s The Master of Petersburg, focusing on the fictionalized figure of F.M. Dostoevsky. The study analyzes how the author’s personal guilt and the loss of his stepson, Pavel, trigger a descent into a psychological underworld. Through intertextual links to Crime and Punishment, writing is depicted as a demonic act of betrayal and exorcism. Ultimately, literature remains the only path toward salvation and immortality. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.